Factors Of Domestic Violence When Movement Control Orders - Azura Binti Md Zahari; PM Dr Faizah Binti Abdul Ghani (Green Publisher Indonesia, 2021)
Cases of Domestic Violence were increasing when the Movement Control Order was implemented in March 2020. This is becoming increasingly worrying and needs to be given attention by all parties. This is because domestic violence can affect family institutions in society. Domestic violence is one of the patterns of coercive behavior that can have a detrimental effect on the victim that can cause severe physical and emotional injuries such as trauma and suicide. Therefore this article discusses the factors of domestic violence that can occur against women during the Movement Control Order. This study used a library research method that aims to examine the factors faced by women during the period of the Movement Control Order is implemented. The result of this research concluded that violence against women needs to be given serious attention because women are an important asset to the State. Violence against women also needs to be addressed by identifying the causes of violence to prevent women from continuing to be victims of violence. The effects of violence on women such as suffering from physical injuries and health problems as well as trauma due to mental and emotional disorders.